Contesting Sharia and Human Rights in the Digital Sphere: Media Representations of the Caning Controversy under the Qanun Jinayat in Aceh - Hakim, Putri Rahmah Nur; Abdullah, Irwan; Musfiroh, Mayadina Rohmi; Sintang, Suraya; Razick, Ahamed Sarjoon (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
The controversy surrounding the implementation of Aceh’s Qanun No. 6 of 2014 on Islamic Criminal Law (Qanun Jinayat), particularly regarding corporal punishment through public caning, has been extensively examined from normative and political perspectives. However, scholarly attention remains limited in exploring how this issue is represented and reproduced within digital media spaces, despite the increasing significance of online platforms in shaping public opinion and negotiating legal meaning in a digitalized society. This article analyzes how online media narratives frame the enforcement of Qanun Jinayat and how digital discourses reflect and influence public perceptions of the legitimacy, ethics, and effectiveness of Islamic criminal law amidst tensions between local religious values and universal human rights principles. Employing a netnographic approach combined with framing discourse analysis, the study examines national and international online news articles published between November 2024 and January 2025, through the lens of three legal dimensions: law in the idea, law in the book, and law in action. The findings reveal stark narrative polarization: local media emphasize religio-cultural legitimacy and procedural legality grounded in special autonomy, while international media and human rights organizations highlight discriminatory practices, inconsistent implementation, and violations of individual rights. This study demonstrates that digital media function not merely as information conduits, but as discursive agents that actively shape, contest, and reconstruct the legal and moral legitimacy of Sharia in contemporary Indonesia. Consequently, Qanun Jinayat must be understood not only as a legal text but as a socially negotiated construct within the digital public sphere. [Kontroversi mengenai implementasi Qanun Aceh No. 6 Tahun 2014 tentang Hukum Jinayat, khususnya dalam aspek hukuman cambuk publik, telah banyak dikaji melalui pendekatan normatif dan politis. Namun, representasi dan reproduksi isu ini dalam ruang media digital masih merupakan area yang relatif terabaikan, padahal media online memainkan peran sentral dalam pembentukan opini publik serta negosiasi makna hukum dalam masyarakat yang semakin terdigitalisasi. Artikel ini menganalisis bagaimana narasi media online membingkai pelaksanaan Qanun Jinayat, serta bagaimana wacana digital mencerminkan dan memengaruhi persepsi publik terhadap legitimasi, etika, dan efektivitas hukum syariah dalam konteks ketegangan antara nilai-nilai religius lokal dan prinsip-prinsip hak asasi manusia universal. Dengan menggunakan metode netnografi dan framing discourse analysis terhadap sejumlah artikel media daring nasional dan internasional selama periode November 2024–Januari 2025, penelitian ini mengkaji tiga dimensi hukum: law in the idea (konsep), law in the book (norma hukum), dan law in action (praktik). Temuan menunjukkan adanya polarisasi narasi yang tajam antara media lokal yang cenderung menekankan legitimasi religius-kultural dan legalitas prosedural berbasis otonomi khusus, dan media internasional serta lembaga hak asasi manusia yang menyoroti praktik diskriminatif, inkonsistensi implementasi, serta pelanggaran terhadap hak-hak individu. Penelitian ini menunjukkan bahwa media digital tidak sekadar berfungsi sebagai saluran informasi, tetapi sebagai aktor diskursif yang aktif dalam membentuk, mempertarungkan, dan merekonstruksi legalitas serta legitimasi moral syariah di Indonesia kontemporer. Dengan demikian, Qanun Jinayat harus dipahami tidak hanya sebagai teks hukum, melainkan sebagai konstruksi sosial yang senantiasa dinegosiasikan dalam ranah publik digital.]